2013
DOI: 10.4236/ojmp.2013.21003
|View full text |Cite
|
Sign up to set email alerts
|

Medically Unexplained Symptoms (MUS): What Do Current Trainee Psychologists, Neurologists and Psychiatrists Believe?

Abstract: Objectives: Medically unexplained symptoms (MUS) are common in all medical settings. These conditions remain controversial, aetiology remains poorly understood and treatments have been slow to develop. This study aimed to examine the beliefs held by psychologists and other professionals about MUS, which may impact upon clinical practice. Design: 375 clinical psychology trainees from 23 UK training courses, 12 neurologists and 19 psychiatrists in training completed a weblink survey designed to elicit a range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Despite these critical articles, many psychologists, especially clinical and counseling psychologists, continue to harbor the idea that traumatic memories can be buried for years or decades in the unconscious and later recovered. Magnussen and Melinder (2012) surveyed licensed psychologists and found that 63% ( n = 540) believed recovered memories to be “real.” Kemp, Spilling, Hughes, and de Pauw (2013) demonstrated that 89% ( n = 333) of surveyed clinical psychologists believed that memories for childhood trauma (such as sexual abuse) can be “blocked out” for many years. Patihis et al (2014) found that 60.3% ( n = 35) of clinical practitioners and 69.1% ( n = 56) of psychoanalysts agreed that traumatic memories are often repressed.…”
Section: Memory Beliefs About Repressed Memories: From Then To Nowmentioning
confidence: 99%
“…Despite these critical articles, many psychologists, especially clinical and counseling psychologists, continue to harbor the idea that traumatic memories can be buried for years or decades in the unconscious and later recovered. Magnussen and Melinder (2012) surveyed licensed psychologists and found that 63% ( n = 540) believed recovered memories to be “real.” Kemp, Spilling, Hughes, and de Pauw (2013) demonstrated that 89% ( n = 333) of surveyed clinical psychologists believed that memories for childhood trauma (such as sexual abuse) can be “blocked out” for many years. Patihis et al (2014) found that 60.3% ( n = 35) of clinical practitioners and 69.1% ( n = 56) of psychoanalysts agreed that traumatic memories are often repressed.…”
Section: Memory Beliefs About Repressed Memories: From Then To Nowmentioning
confidence: 99%
“…For example, Kemp et al (2013) showed that 89% (n ¼ 333) of surveyed clinical psychologists endorsed the belief that traumatic memories of childhood abuse could be blocked for many years. Also, Patihis et al (2014) showed that 60.3% (n ¼ 35) of clinical practitioners and 69.1% (n ¼ 56) of psychoanalysts believed that traumatic memories are frequently repressed.…”
Section: Believing In Repressed Memorymentioning
confidence: 99%
“…MUPS are commonly encountered across all healthcare settings. 2 , 3 Analyses from the United Kingdom have estimated that MUPS is the presenting problem for around 22% of primary care attendances and 8% of inpatient bed days. 4 , 5…”
Section: Introductionmentioning
confidence: 99%